2004
DOI: 10.1007/bf03166511
|View full text |Cite
|
Sign up to set email alerts
|

Basic characteristics of the a-SiOC∶H thin films prepared by PE CVD

Abstract: Hydrogenated amorphous silicon oxycarbide (a-SiOC:H) thin films were prepared by plasmaenhanced chemical vapor deposition (PE CVD) using an RF helical coupling pulsed-plasma system. Films of the thickness ranging from 210 nm to 1.4 μm were deposited on silicon wafers from vinyltriethoxysilane (VTES) precursor. The thickness of plasma-polymerized films was measured by a Profilometer Talystep using a defined scratch in the layer as deep as the substrate. The deposition rate was observed with respect to the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The evolution of Si-O-Si and Si-O-C Phenyl bonds was measured at the wavenumber range of 900~1200 cm −1 from the Fourier Transform-Infrared (FT-IR) spectra ( Fig. 2d ) 43 , which also delivered the gradual increase in the aromatic C-C and C = C peaks with respect to the PVP content 44 .…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of Si-O-Si and Si-O-C Phenyl bonds was measured at the wavenumber range of 900~1200 cm −1 from the Fourier Transform-Infrared (FT-IR) spectra ( Fig. 2d ) 43 , which also delivered the gradual increase in the aromatic C-C and C = C peaks with respect to the PVP content 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Prior work has shown that other bonding types including Si-H, C-H, Si-Si, and C-O are commonly found in these materials [31,[35][36][37][38] and will dramatically affect the results of this method of estimating excess carbon independent of the degree of carbon-carbon bonding present. The presence of hydrogen in particular can dramatically affect the stability of the structure [35,39,40].…”
Section: Resultsmentioning
confidence: 99%